How Do Public Perceiv of Branchless Banking Through Brilink Agents? A Field Research in Kaliputu Kudus Village - Alina Rusda; violanita angga astrini; Kharis Fadlullah Hana (Kunuz: Journal of Islamic Banking and Finance, 2022)
Improving banking services is useful for attracting customer interest and creating new features and products through quality technology. However, some Indonesians still do not know how to use sophisticated and efficient banking services, especially people who live far from the office. This study aims to solve public perceptions of the existence of branchless banking through aspects of trust, service quality, and facilities provided by BRILink. The method used is qualitative with a phenomenological approach. The data in this study were obtained through interviews and observations with BRILink owners and customers in the Kaliputu area. This study focuses on public perceptions of user convenience, usability, and risk on the BRILink. This study reveals that informants using BRILink have met the trust indicators, service quality, and facilities at BRILink agents. These three indicators give rise to public perceptions regarding the ease of use, the benefits of services, and the risks that exist in BRILink. Service quality is the clearest indicator in BRILink services. It is recommended that indicators regarding public perception of BRILink should be improved so that further research can be maximized.